Facing the strain. - Neville-Neil, George (New York ACM, 2006)
A koder with attitude, KV answers your questions. Miss Manners he ain't.
Keywords: Software; Software engineering; Distribution, maintenance and enhancement; Version control; Management; Software configuration management